Stachys hakkariensis (Lamiaceae), a new species from eastern Anatolia (Turkey) belonging to Stachys sect. Olisia - Akçi̇çek, Ekrem; Firat, Mehmet; Güner, Özal (Phytotaxa, 2016)
Stachys hakkariensis, a new species of S. sect. Olisia, is described and illustrated from eastern Anatolia, Turkey. From the morphological point of view, S. hakkariensis appears to be similar  to S. sparsipilosa, but it differs in several morphological features regarding the stem, leaves, flower and fruit. Geographical distribution, habitat and IUCN conservation status of this species are provided.